THE INFLUENCE OF SOCIODEMOGRAPHIC FACTORS ON THE DEVELOPMENT OF ANXIETY A CORONAVIRUS DISEASE PANDEMIC - Jandric-Kocic, Marijana; Knezevic, Snezana (HEALTH CARE, 2020)
Introduction/Aim: The COVID-19 pandemic poses a serious threat to global mental health. Fear ofdeath, social distancing, economic problems, changes in the education system, and cessation of normaldaily functioning induce psychiatric disorders, primarily anxiety. The research aimed to determine theinfluence of sociodemographic factors on the development of anxiety during the COVID-19 pandemic.Methods: The cross-sectional study, over two months, included 200 persons without symptoms ofCOVID-19, 60.0% of women and 40.0% of men, with an average age of 51.0 ± 9.2 years. One hundredpeople reported to the family medicine clinic of the Health Care Center Krupa on the River Una forexaminations or administrative reasons, and another hundred were accompanied by them. In additionto the general questionnaire, the Generalized Anxiety Disorder-7 (GAD-7) Self-Assessment SymptomIntensity Questionnaire was used. The χ2- test and Fisher's test were used for the statistical analysis.Discussion: 105 (52.5%) participants included in the study had symptoms of anxiety (35.0% mildsymptoms of anxiety, 15.5% moderate symptoms of anxiety, 2.0% severe symptoms of anxiety). Anxietywas slightly more common in men (56.2%) than in women (50.0%), as well as in the oldest (60-79 years)(92.6%) than in younger participants (12.5% for age 20-39 and 44.7% for ages 40-59). The frequencyof anxiety was lower in persons with higher (33.3%) than lower education (44.5% of participants withprimary and 46.6% of participants with high school). A slightly higher frequency of anxiety was amongthe employed (69.5%) than among the unemployed (43.0%), as well as among persons living in urban(80.8%) in comparison to those living in rural (42.6%) areas. Anxiety problems were experienced by51.3% of participants living in marriage or extramarital union and 56.8% of participants who were notmarried or in an extramarital union. People with anxiety were significantly more likely to be aged 60-79than people without anxiety. There were no significant differences between these groups in terms ofgender, level of education, employment, place of residence and marital status of the participants.Conclusion: Every other person in this study had some form of anxiety. Further research in this areaand proposing adequate prevention programs are needed.
Keywords: COVID-19, pandemic, anxiety, risk factors